Experimental Study of a Combined Machine-Tractor Unit Carried out under Real Field Conditions - Bulgakov, Volodymyr; Aboltins, Aivars; Rucins, Adolfs; Beloev, Hristo; Nadykto, Volodymyr; Kyurchev, Volodymyr; Adamchuk, Valerii; Kaminskiy, Viktor (Current Research Progress in Agricultural Sciences Vol. 3, 2024)
Experimental investigations have been carried out on a combined machine and tractor unit, based on the wheeled integral tractor of Class 3, which simultaneously performs two technological operations. The first operation is the disintegration of the plant residues that may be in the form of corn or sunflower stubble. This operation is performed by an active rotary chopper, mounted in front of the tractor. The second operation is ploughing to a preset depth with the simultaneous introduction of the crushed plant residues into the soil. The second operation is performed by a five-body plough, mounted behind the tractor. The active working parts of the frontally mounted disintegrator, which is a rotor with knives pivotally mounted on the drive shaft, are driven into rotation using the front power take-off shaft of the tractor, which has two operating modes: 540 and 1000 rpm. The rear-mounted five-body plough operates, as usual, with a preset ploughing depth. The purpose of the investigation was to establish the degree of impact of the soil parameters (hardness, moisture, surface unevenness) and the parameters of the frontally mounted disintegrator upon the vibrations of the aggregating tractor and, in general, on the quality indicators of the operation of the entire machine and tractor unit, i.e. the quality of ploughing and introduction of the plant residues into the soil. It has been established by experimental field studies that, to reduce the dynamic load in the drive of the working parts of the crop residue disintegrator and to achieve high-quality disintegration of these residues with subsequent covering them with soil, the front power take-off shaft of the tractor must be adjusted to a rotation speed of 1000 rpm. In such a mode of rotation of the disintegrator rotor, the difference in the dispersion of its vertical vibrations and the vibrations of the front axle of the aggregating tractor is insignificant. It is no coincidence that the dispersion of fluctuations in the depth of ploughing (1.44 cm2), which changes aperiodically in the frequency range 0-2.5 Hz, is less than the dispersion of fluctuations in the unevenness of the longitudinal field profile (2.75 cm2). As a result of processing the experimental data, it was found that the fluctuations in the traction resistance of a rear-mounted plough had the least impact on the fluctuations in the ploughing depth. This is evidenced by the small value of the cross-correlation function: for such an oscillatory process as “the plough traction resistance – the ploughing depth”, it was 0.22, which is 3.4 times less than for the oscillatory process “the longitudinal profile of the soil surface – the ploughing depth". The number of crushed particles of the plant residues less than 15 cm in length increased by 1.5 times, and the number of particles more than 30 cm in length decreased by 3 times. Besides that, the complete introduction of the disintegrated plant residues into the soil was observed. As a result of the experimental investigation, their uncrushed part was quite insignificant and did not exceed 1%. The data, obtained from field experimental studies, showed positive results, which indicates the prospects of using such a combined machine and tractor unit.